2022
DOI: 10.1177/10783903221083260
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Lifetime History of Abuse and Trauma With Opioid Use Disorder: Implications for Nursing Assessment and Care

Abstract: Background: Opioid use disorder (OUD) is a public health crisis and is challenging to treat. Previous research has shown correlations between OUD, abuse/trauma, and chronic pain. Aims: The purpose of this study was to investigate history of lifetime sexual, physical, and/or emotional abuse among participants in a medication-assisted treatment (MAT) program for OUD, and to investigate associations between abuse history and chronic pain. Methods: This is a secondary analysis of intake data from a 2-year, nonexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Our primary concern about the proposed treatment pathway is the lack of an explicit effort to measure and address physical and psychological trauma. Patients with OUD entering treatment, particularly low-threshold treatment settings, often live in dangerous environments that can be traumatizing (Driscoll Powers et al, 2022). Sexual violence and coercion are common and often ongoing.…”
Section: What Factors Might Facilitate or Hinder The Uptake Implement...mentioning
confidence: 99%
“…Our primary concern about the proposed treatment pathway is the lack of an explicit effort to measure and address physical and psychological trauma. Patients with OUD entering treatment, particularly low-threshold treatment settings, often live in dangerous environments that can be traumatizing (Driscoll Powers et al, 2022). Sexual violence and coercion are common and often ongoing.…”
Section: What Factors Might Facilitate or Hinder The Uptake Implement...mentioning
confidence: 99%
“…Studies specific to examining trauma among those treated with MOUD have been relatively limited in scope and/or small in sample size. For example, one study (N = 919) examined interpersonal trauma only (physical, sexual, or emotional abuse) and found that 23% reported sexual abuse, 43% physical abuse, and 58% emotional abuse and that there were no differences by gender on any of these categories ( 12 ). Unfortunately, this study by Powers did not distinguish whether the traumatic events occurred in childhood or as adults.…”
Section: Introductionmentioning
confidence: 99%